HIV‐1 Nef disrupts membrane‐microdomain‐associated anterograde transport for plasma membrane delivery of selected Src family kinases. (3rd May 2013) - Pan, Xiaoyu; Geist, Miriam M.; Rudolph, Jochen M.; Nickel, Walter; Fackler, Oliver T.
Summary: HIV‐1 Nef, an essential factor in AIDS pathogenesis, boosts virus replication in vivo . As one of its activities in CD4 + T‐lymphocytes, Nef potently retargets the Src family kinase (SFK) Lck but not closely related Fyn from the plasma membrane to recycling endosomes and the trans‐Golgi network to tailor T‐cell activation and optimize virus replication. Investigating the underlying mechanism we find Lck retargeting involves removal of the kinase from membrane microdomains. Moreover, Nef interferes with rapid vesicular transport of Lck to block anterograde transport and plasma membrane delivery of newly synthesized Lck. The sensitivity of Lck to Nef does not depend on functional domains of Lck but requires membrane insertion of the kinase. Surprisingly, the short N‐terminal SH4 domain membrane anchor of Lck is necessary and sufficient to confer sensitivity to Nef‐mediated anterograde transport block and microdomain extraction. In contrast, the SH4 domain of Fyn is inert to Nef‐mediated manipulation. Nef thus interferes with a specialized membrane microdomain‐associated pathway for plasma membrane delivery of newly synthesized Lck whose specificity is determined by the affinity of cargo for these sorting platforms. These results provide new insight into the mechanism of Nef action and the pathways used for SFK plasma membrane delivery. Abstract : HIV‐1 Nef hijacks host cell sorting and signaling machineries to optimize virus replication in the infected host. This study addresses the mechanism by which Nef alters the subcellular localization of the Src family kinase Lck to tailor the responsiveness of infected CD4+ T lymphocytes to T cell activation. We report that Nef blocks plasma membrane delivery of specialized membrane microdomain sorting platforms to which cargo such as Lck associates via SH4‐domain membrane anchors. These results provide novel insight into the mechanisms of Nef action and anterograde transport of SH4 domain containing proteins.